Update TFCC: histology and pathology, classification, examination and diagnostics - Kirchberger, Michael Constantin; Unglaub, Frank (Archives of orthopaedic and trauma surgery, 2015)
The TFCC is a crucial stabilizer of the DRUJ. Based on its superficial and deep fibers, the TFCC guarantees unrestricted pronation and supination which is essential for performing sophisticated tasks. The ability to perform complex movements is of uppermost importance for hand function. Therefore, a functional intact TFCC is a prerequisite in this context. The articular disc of the TFCC is a fibrocartilaginous extension of the superficial zone of hyaline articular cartilage which arises from the radius. The peripheral 10–40 % of the TFC is vascularized. Degeneration of the articular disc is common with increasing age. Even though the central part of the articular disc is avascular, potential regeneration of lesions could be detected. The Palmer and Atzei classifications of TFCC lesions are complementary. TFCC innervation is based on different nerves. There is a high variability. A diligent clinical examination facilitates specific tests which help to allocate symptoms to the pathology. Therefore, a thorough clinical examination is not dispensable. Wrist arthroscopy remains the “gold standard” for diagnosing TFCC pathologies despite technical progress in imaging modalities. MR arthrography may have the potential to become a real alternative to wrist arthroscopy for diagnosing TFCC pathologies with technical progress in the future.